Controlled delivery of basal insulin from phase-sensitive polymeric systems after subcutaneous administration: in vitro release, stability, biocompatibility, in vivo absorption, and bioactivity of insulin - Al-Tahami, Khaled; Oak, Mayura; Singh, Jagdish (Elsevier, 2011)
The purpose of this study was to investigate the phase-sensitive delivery systems (D,L-polylactide in triacetin) for controlled delivery of insulin at basal level. The effect of varying concentration of zinc, polymer, and insulin on the in vitro release of insulin was evaluated. Stability of released insulin was investigated by differential scanning calorimetry, circular dichroism, and matrix-assisted laser desorption/ionization time of flight mass spectrometry. In Vivo insulin absorption and bioactivity were studied in diabetic rats. In vitro and In Vivo biocompatibility of delivery systems were evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay and skin histology, respectively. Extended release profiles of insulin for 2, 4, and 8 weeks from delivery systems containing 20%, 30%, and 40% (w/v) polymer concentration was observed. A ratio of 1:5 insulin hexamer to zinc was shown to be optimum. Physical and chemical stability of released insulin was greatly conserved. In Vivo studies demonstrated controlled release of insulin with reduction in blood glucose for approximately 1 month. In vitro and In Vivo studies demonstrated that the delivery system was biocompatible and controlled the delivery of insulin for longer durations after single subcutaneous injection.